Modelling of Moisture Loss and Oil Uptake During Deep-Fat Frying of Plantain (Dodo) - Adeyanju, J. A.; Olajide, J. O.; Oke, E. O.; Adedeji, A. A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
In this study, model was developed to predict moisture loss and oil uptake during deep-fat frying of plantain (dodo). Plantain samples were sliced and fried at different frying temperatures (150, 160, 170, 180 and 190 °C) in a deep fryer for periods varying from 2 to 4 min. Moisture and fat analyses were determined based on the AOAC standard method. Mathematical model was developed from fundamental law of mass diffusion with the aim of predicting moisture loss and oil uptake rate during DFF of dodo. The model was solved numerically using explicit Finite Difference Technique (FDT). Computer codes were written in MATLAB environment for moisture loss and oil uptake in the slices at different frying conditions. The predicted results were compared with experimental data and good agreement was obtained. The correlation coefficients between the predicted and experimental values of moisture and oil transfer models ranged from 0.988 to 0.994 and 0.958 to 0.978, respectively. The results show that the model is consistent and it may be used to predict moisture loss and oil uptake during deep-fat fried of dodo.